Notes in colombian herpetology, iii (1944)
In my recent paper on American Caecilians (Dec. 1942, Bull. Mus. Camp. Zool. 91, 6) the six then known specimens of Gymnopis from Colombia were regarded as of one species, G. nicefori Barbour, with a range from Cáceres in the Lower Cauca in northern Antioquia (alt. 150 m.) to Honda, Girardot and San Juan de Rioseco (alt. 1300 m.) in the Upper Magdalena valley. Later examination of four additional specimens from the Upper Magdalena valley, Honda (3) and Aguas Blancas in Tolima, seemed to confirm this view. It is therefore with some surprise that I find that a specimen of Gymnopis, taken by me at EI Centro, in the Central Magdalena valley, on Dec. 24, 1943, is not nicefori, and must be described as new. I name it in honor of my friend Wilfred Devereux Price, Esq., to whom I am indebted for kind assistance and hospitality at EI Centro.